Remanufacturing as a means for achieving low-carbon SMEs in Indonesia - Fatimah, Y.; Biswas, Wahidul (2016)
Remanufacturing can reduce the energy intensity and associated greenhouse gas (GHG) emissions significantly and increase the eco-efficiency of product systems by utilizing recovered end-of-life parts. This paper presents the GHG mitigation potential of technically feasible remanufactured alternators in Indonesian small- and medium-sized enterprizes. Life cycle assessment approach and Weibull ++8 software have been used to calculate environmental and quality parameters. Since existing remanufactured alternators have not been found to meet the technical criterion for customers’ satisfaction, a number of alternative remanufacturing strategies have been explored to identify an option that has not only reduced GHG emissions but also has satisfied reliability, durability and warranty period criterion. Three improvement scenarios involving three different remanufacturing strategies were investigated in this case study, and yielded useful insights in order to come up with a technically feasible remanufacturing strategy for reducing a significant amount of GHG emissions. The improvement scenario III, which maximizes the use of used components, was found to offer technically and environmentally feasible remanufacturing solutions. Overall, this research has found that about 7207 t of CO2 -eq GHG emissions and 111.7 TJ embodied energy consumption could potentially be avoided if 10 % of alternators in Indonesian automobile sector are remanufactured using technically feasible remanufacturing strategy.